Comparative Therapeutic Effects of Natural Compounds Against Saprolegnia spp. (Oomycota) and Amyloodinium ocellatum (Dinophyceae) - Tedesco, Perla; Beraldo, Paola; Massimo, Michela; Fioravanti, Maria Letizia; Volpatti, Donatella; Dirks, Ron; Galuppi, Roberta (Frontiers in Veterinary Science, 2020)
The fish parasites Saprolegnia spp. (Oomycota) and Amyloodinium ocellatum (Dinophyceae) cause important losses in freshwater and marine aquaculture industry, respectively. The possible adverse effects of compounds used to control these parasites in aquaculture resulted in increased interest in the search for natural products with antiparasitic activity. In this work, eighteen plant-derived compounds (2',4'-Dihydroxychalcone; 7-Hydroxyflavone; Artemisinin; Camphor (1R); Diallyl sulfide; Esculetin; Eucalyptol; Garlicin 80%; Harmalol hydrochloride dihydrate; Palmatine chloride; Piperine; Plumbagin; Resveratrol; Rosmarinic acid; Sclareolide; Tomatine, Umbelliferone and Usnic Acid) have been tested in vitro. Sixteen of these were used to determine their effects on the gill cell line G1B (ATCC ® CRL-2536TM) and on the motility of viable dinospores of Amyloodinium ocellatum, and thirteen were screened for inhibitory activity against Saprolegnia spp. The cytotoxicity results on G1B cells determined that only two compounds (2',4'-Dihydroxychalcone and Tomatine) exhibited dose-dependent toxic effects. The highest surveyed concentrations (0.1 and 0.01 mM) reduced cell viability by 80%. Upon lowering the compound concentration the percentage of dead cells was lower than 20%. The same two compounds revealed to be potential antiparasitics by reducing in a dose-dependent manner the motility of A. ocellatum dinospores up to 100%. With respect to Saprolegnia, a Minimum Inhibitory Concentration was found for Tomatine (0.1 mM), Piperine and Plumbagin (0.25 mM), while 2',4'-Dihydroxychalcone considerably slowed down mycelial growth for 24 h at a concentration of 0.1 mM. Therefore, this research allowed to identify two compounds, Tomatine and 2',4'-Dihydroxychalcone, effective against both parasites. These compounds could represent promising candidates for the treatment of amyloodiniosis and saprolegniosis in aquaculture. Nevertheless, further in vitro and in vivo tests are required in order to determine concentrations that are effective against the considered pathogens but at the same time safe for hosts, environment and consumers.